Analisis Antologi Puisi Pesan Tua Karya Hendra Djafar Menggunakan Teori Semiotic - Abdul Muttalib; Wahyuddin Wahyuddin; Rina Riniawati (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2021)
This study aims to analyze the poetry anthology "Old Message" by Hendra Djafar using structuralism-semiotic theory. This type of qualitative descriptive research by conducting library research (library research) through relevant reading materials. The analysis was carried out on three poems, “I am a Orderly Poetry,” “Salawatku,” and "Old Message" which are considered to represent the tendencies of Hendra Djafar's poetry in the types of ballads, odes and contemporary. The analysis of the three poems is then analyzed using the theory analysis are: 1). The dimensions of the icon are analyzed from the power of saying "I" lyrics as a poet as well as acting as a dominant-looking narrator, 2). The index dimension implies that there is tension between the form and content of the poem, contradictions in the psychological dimension between messages and impressions, as well as between exclamations and criticisms, 3). Although the dimensions of arbitrary symbols are not widely found.